La motivación y su influencia en el nivel del aprendizaje en el área de matemática de la Escuela de Educación Básica “La Maná” - Chichande Molina, Galud Pensilvania (2021)
The research project is aimed at strengthening the mathematics learning system of middle school students, for this reason it is established as a general objective to determine the influence of motivation in the learning of the mathematics area of middle school students of the School of Basic Education "La Maná" to strengthen the development of learning through a guide of motivating activities, because the educational process is a set of elements that interact dynamically to achieve goals and objectives, raised within each of the subjects, promoting comprehensive and collective learning in relation to the needs of each of the students, The methodology used in the development of the activities is based on the analysis of reality and the development of a viable proposal that allows to dynamize the educational work, for this reason the elaboration and application of motivational activity guides for the learning of mathematics was established as a proposal; The motivational guides in order to maintain a degree of acceptance and pedagogical support have passed through a validation filter of specialized people, which have made their application feasible in the pedagogical field, concluding that the guide is decisive in the development of learning according to According to the criteria issued by specialists and applied to users, it is evident that since there is a higher degree of permanent motivation, the development of mathematics learning is significant, which contributes to the educational process at the institutional level.